Osmosis‐Powered Hydrogel Microneedles for Microliters of Skin Interstitial Fluid Extraction within Minutes. Issue 10 (30th April 2020) - Zheng, Mengjia; Wang, Zifeng; Chang, Hao; Wang, Lulu; Chew, Sharon W. T.; Lio, Daniel Chin Shiuan; Cui, Mingyue; Liu, Linbo; Tee, Benjamin C. K.; Xu, Chenjie
Abstract: Hydrogel microneedle patch enables the extraction of skin interstitial fluid (ISF) through in situ swelling in a minimally invasive manner without assistance of mechano‐chemical peripherals. However, existing hydrogel microneedles require tens of minutes with multistep process to collect sufficient volume (1 mL) for effective analysis. This study introduces an osmolyte‐powered hydrogel microneedle patch that can extract ISF three times faster than the existing platforms and provide in situ analysis of extracted biomarkers. The microneedle patch is composed of osmolytes (i.e., maltose) and hydrogel (i.e., methacrylated hyaluronic acid). During the extraction process, the osmolytes dissolve in the matrix and provide the osmotic pressure that increases the diffusion of ISF from skin to the hydrogel matrix. A patch with 100 microneedles can extract 7.90 µL of ISF from pig skin ex vivo and 3.82 µL of ISF from mouse skin in vivo within 3 min, whereas the control (i.e., hydrogel microneedle without osmolytes) requires >10 min to achieve similar results. The extracted ISF allows the quantification of biomarkers such as glucose and/or drugs such as insulin in vivo. Through the integration with the electronic glucose sensors, the whole system permits the direct and rapid analysis of the extracted glucose. Abstract : An osmolyte‐powered hydrogel microneedle patch is designed to extract microliters of skin interstitial fluid (ISF) within minutes which is three times faster than the existing platforms. This patch can extract 7.90 µL of ISF from pig skin ex vivo and 3.82 µL of ISF from mouse skin in vivo within 3 min and allow the in vivo quantification of biomarkers.